If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3/4)x+(5/4)=-(7/4)
We simplify the equation to the form, which is simple to understand
(3/4)x+(5/4)=-(7/4)
Simplifying:
( + 0.75)*x+(5/4)=-(7/4)
Simplifying:
( + 0.75)*x+(+1.25)=-(7/4)
Simplifying:
( + 0.75)*x+(+1.25)=-(+1.75)
Reorder the terms in parentheses
( + 0.75x)+(+1.25)=-(+1.75)
Remove unnecessary parentheses
+ 0.75x+(+1.25)=-(+1.75)
Remove unnecessary parentheses
+ 0.75x+1.25=-(+1.75+)
Remove unnecessary parentheses
+ 0.75x+1.25=-1.75
We move all terms containing x to the left and all other terms to the right.
+ 0.75x=-1.75-1.25
We simplify left and right side of the equation.
+ 0.75x=-3
We divide both sides of the equation by 0.75 to get x.
x=-4
| y^2-3y-12=0 | | -4y-23=6y+17 | | 5x+4=-4+3x+14 | | 4(3x+7)=64 | | 2m+5=4m-4 | | r-3/10=r/16 | | -6(x-5)+3=33 | | 5-7x=104-28x | | 6x+8=15x-9 | | 18x+27=6x-2 | | 6x^2-15x-126=0 | | x(5-x)+4(x^2+1)= | | 5x+10=4x-4 | | 2x-5y=12 | | 4x+7=47 | | 9v-40=v-24 | | 20x-3=40x+1 | | x*.80=30 | | c=800x+90000 | | 0.4(x-3)=0.75x-5 | | 25-2(4x+2)=7x-2(5x-1) | | 8x+5=67 | | -2p-3(2-4p)=5(p-6)-21 | | -4(x+2)=6(x+6)-5 | | a/5=45/15 | | 2x-(5x+2)=12+5(x-1) | | 6b^2+24b-30=0 | | 3.5x-1=-1/2(-7x+2) | | 5y+20=3y-12 | | 18x-4-14x=2(2x-4)+4 | | 6(3x-1)-6=-4x+3(3x-8) | | 18x(-14x)= |